Effect of Spinal Anesthesia on Blood Pressure During Cesarean Section in Private Indonesian Hospital - Nanmi, Nassya Putri; Lailly, Husnul; Armyanti, Ita; Novitarini, Poppy; Handoko, Willy (Majalah Kedokteran Bandung, 2025)
The 2018 Indonesian Basic Health Research Data presented an increase in the number of cesarean sections from the previous years, with an increase of 17.6%. In Anugerah Bunda Khatulistiwa Hospital, a private hospital in Pontianak, Indonesia, cesarean section was performed in 689 and 641 cases in 2021 and 2022, respectively. This trend highlights the importance of understanding the anesthesia methods used during this procedure, including spinal anesthesia. Despite the common use of this type of anesthesia, spinal anesthesia an cause changes in the maternal blood pressure. This study aimed to determine the effect of spinal anesthesia on patients’ blood pressure during cesarean section. This retrospective observational analytical study was conducted at the Anugerah Bunda Khatulistiwa Hospital Pontianak, Indonesia, from May 2023 to January 2024. Medical records were selected from 246 patients using consecutive sampling method. Most patients aged between 27 and 29 years, with 207 were in the productive age group (20-35 years). The mean weight was 72.77 kg (±10.43) and the mean height was 156.70 cm (±5.85). The majority were overweight based on the BMI score (n=111), and the spinal anesthesia dose used was 15 mg bupivacaine. The Friendman test on the systolic and diastolic blood pressures before and after anesthesia to determine the effect of spinal anesthesia on blood pressure. The results showed a p-value of 0.000 (p<0.05) for both systolic and diastolic observations. This indicates that spinal anesthesia influences the blood pressure of patients undergoing cesarean sections under spinal anesthesia.